2003
DOI: 10.1097/01.brs.0000067089.83472.1f
|View full text |Cite
|
Sign up to set email alerts
|

Back to Work: Predictors of Return to Work Among Patients With Back Disorders Certified As Sick

Abstract: Information about the age of the patients, diagnoses, pain intensity, self-assessed work ability, and self-predicted absence status may be used as predictors of time until return to work in patients with back disorders certified as sick who attend a back disorder outpatient clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…The same result was found earlier for Norwegian patients with back disorders who had been certified as sick (Reiso et al, 2003). The authors of that study suggested that work ability questions may be related more to function in a setting of sickness certification than a global quality of life question and therefore be more predictive.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The same result was found earlier for Norwegian patients with back disorders who had been certified as sick (Reiso et al, 2003). The authors of that study suggested that work ability questions may be related more to function in a setting of sickness certification than a global quality of life question and therefore be more predictive.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, recent empirical studies have indicated the importance of patients' expectations of recovery as good predictors of return-to-work and rehabilitation independent of diagnosis and treatment (Ekbladh et al, 2004;. Studies in other disorders have also shown that a patient's own assessment of work ability (Reiso et al, 2003), expectation of job success (Ekbladh et al, 2004) and work recovery expectations (Hogg-Johnson and Cole, 2003;Nieuwenhuijsen et al, 2006;Turner et al, 2006) do predict return-to-work.…”
mentioning
confidence: 99%
“…A well-established predictor of future health and return to work is the sick-listed person's own expectation of future return to work [11][12][13][14]. In a systematic review, Mondloch et al [15] found consistent associations between patients' recovery expectations and health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the information can be predictor of time until RTW in participants with LBP certified as sick who attend a back disorder outpatient clinic (Reiso, 2003). After 2 years the participants were invited to a new complete check.…”
Section: Interventionsmentioning
confidence: 99%